Legal Protection for the Employment Status of Judicial Commission Liaisons - Amalia, Riska Ari; Umam, Khairul; Rahmadani, Rahmadani; Fallahiyan, Muh. Alfian (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The discourse on the status of liaisons and institutional employees is not recognized in the Law on State Civil Servants or the Law on Employment, thus giving rise to problems, namely the recognition of the employment status of liaisons in each region. The formulation of the problem raised is legal protection of the employment status of liaisons. The method used in this research is the normative legal research method. The approach used is a statutory approach (statute approach) and conceptual approaches (conceptual approach). In conclusion, the absence of norms explaining the employment status of liaisons has implications for the absence of liaison personnel management arrangements, indicating that legal protection for the employment status of liaisons is not yet effective. The suggestion that can be given is that countries can convert liaisons into part of ASN through a series of tests, regulations and policy regulations as guidelines.